STRATEGI PEMBERDAYAAN NELAYAN KECIL DI INDONESIA - Heru Dian Setiawan (Jurnal Ilmu dan Budaya, 2020)
This research based on the low level of welfare of small fishermen amid increasing Indonesian exports, so that it is not in accordance with the objectives stated in the 2011-2025 Republic of Indonesia Master Plan so that Indonesia can become a developed country with development and welfare outcomes that can be enjoyed equally by all people, and the utilization of marine resources for economic development and the welfare of fishermen and coastal communities. Therefore, through a qualitative process approach and the concept of Rokhmin Dahuri (2012), this study aims to find out strategies to improve the empowerment of small fishermen in Indonesia.